Techniques for detecting genetically modified crops and products - Tripathi, L. (African Journals Online, 2005)
The cultivation of genetically modified crops is becoming increasingly important; more traits are emerging and more acres than ever before are being planted with GM varieties. The release of GM crops and products in the markets worldwide has increased the regulatory need to monitor and verify the presence and the amount of GM varieties in crops and products. Labeling legislation and trade requirements differ from one country to another, leading to the necessity for the development of reliable and sensitive analytical methods for detection, identification and quantification of GM varieties in crops and their products. GM crops and their products can be identified by detecting either the inserted genetic material at DNA level, the resulting protein or phenotype. Several analytical methods such as methods based on the polymerase chain reaction (PCR) for detecting the inserted DNA, immunological assays for detecting the resulting protein, or using bioassays to detect the resultant phenotype have been developed. So far only PCR has found broad application in GMO detection as a generally accepted method for regulatory purposes. Presently, real-time PCR can be considered as the most powerful tool for the detection and quantification of GM crops and products.